La experiencia del teatro digital durante la pandemia por la COVID-19 en Lima - Rebata Delgado, Sofía Magaly (2021)
The COVID-19 pandemic disrupted human coexistence and the alternative to social distancing has been to maintain communication links through technology. With this, gathering in Jorge Dubatti’s terms (2015), a substantial feature of the identity of theater, was affected, and the choice was made for techno-gathering through digital theater. The definition of digital theater and the relationship mediated by technology between scenic artists and audiences are under construction and sustainable management. To analyze the local experience, we have reviewed the situation of Peruvian theater before and during the pandemic and conducted semi-structured interviews with three-stage creators from Lima, who had seasons during the health crisis. Through the qualitative data collected, the strengths, weaknesses, and future scope of this format are identified.